Artificial Mosaic Generation with Gradient Vector Flow and Tile Cutting - Sebastiano Battiato; Alfredo Milone; Giovanni Puglisi (Journal of Electrical and Computer Engineering)
Mosaics are images obtained by cementing together small colored fragments and are an ancient example of discrete primitive-based images. Artificial mosaics are illustrations composed by a set of small images called “tiles” that tessellate a source image aiming to reproduce the original visual information in a mosaic-like style. In this paper, we propose a mosaic generation technique based on gradient vector flow (GVF) together with a set of tile cutting heuristics evaluated according to aesthetic criteria. The effectiveness of the proposed approach has been confirmed by a series of tests and comparisons with state-of-the-art techniques.